SUMMARY OF CONTENT DIRECTIONS OF HISTORY IN THE DEVELOPMENT OF SOCIETY - Quvondiqov Behzodjon Murotbay o‘g‘li; Mustafayev Jafar Shomirzayevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article is dedicated to the study and understanding of the unique importance of history in the development of society. The article describes the content and important trends of history, shows how history is used in the development of society, and in which areas it is important. The article analyzes the political, economic, cultural, religious and social histories related to the important aspects of the development of society.